Identifying digitalization’s impact on how energy sector companies perform environmentally and financially - Kenzhin, Zhaxat; Sabyrzhan, Ali; Mussabalina, Dinara; Kuptleuova, Kenzhessulu; Lelesh, Natalya; Nurbaeva, Aizhan; Shunko, Andrey; Zhakypova, Akmaral; Maralov, Arman (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is energy sector companies in the Republic of Kazakhstan involved in the extraction, transportation, generation, transmission, and distribution of energy resources. The problem addressed is the insufficient understanding of the mechanism through which digitalization affects financial performance, since it remains unclear whether this effect is direct or transmitted through environmental performance indicators. The empirical basis of the study is a balanced quarterly panel dataset for 2015–2025, comprising 220 observations across five companies. Fixed-effects models, a dynamic lagged model, panel vector autoregressive models, and impulse response functions were used in the study. The results show that digitalization has a statistically significant negative effect on carbon intensity in the fixed-effects model (β = −0.2828; p < 0.01), whereas its direct effect on return on assets is not statistically confirmed (β = −0.0035; p > 0.10). Carbon intensity has a significant negative effect on financial performance in both the static fixed-effects model (β = −0.0118; p < 0.01) and the dynamic lagged model (β = −0.00213; p < 0.05). These findings provide indirect empirical support for a possible environmental transmission channel, in which digitalization is associated with a lower environmental burden that may subsequently contribute to financial performance. The study uses quarterly corporate data, a text-based digitalization indicator, and carbon intensity as a measure of environmental performance, allowing an indirect assessment of a possible environmental transmission mechanism. The results can be used by energy companies, regulators, and investors when developing digital transformation and decarbonization strategies and making ESG-related investment decisions